18. FAKTOR-FAKTOR YANG MEMPENGARUHI PERGERAKAN SOSIAL KARMA NIRVANA TERHADAP KEBIJAKAN PEMERINTAH INGGRIS DALAM MENANGGULANGI FENOMENA HONOUR KILLING DI PAKISTAN TAHUN 2003 - 2015 - Mukti, Estu Sarwo; Utomo, Tri Cahyo; Wahyudi, Fendy Eko (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
This research has the focus point on the explanation of transnational crime named honourkilling did by Pakistani immigrants in United Kingdom. Honour killing happens due topatriarchy community who has a culture of honour and shame that discriminate women inorder to be responsible to maintain the honour in the family. This issue has been advocated byKarma Nirvana as a social movement organization which eventually impacted in the creationof United Kingdom government policy to mitigate the problem. The aim of this research is toanswer the question on what are the factors that affect social movement of Karma Nirvanatowards United Kingdom government policy on mitigating honour killing in Pakistan during2003 to 2015. In order to answer that, researcher uses the approach of liberal feminism andresource mobilization theory. The method used for this research is qualitative withexplanative type and data collected by interview and literature review. The result of thisresearch has proven that the factor affected social movement of Karma Nirvana towardsUnited Kingdom government policy are the utilization of resource in the form of formalorganization and the use of honour killing and forced marriage issues which are in line withthe priority of United Kingdom government.